2007
DOI: 10.1523/jneurosci.0307-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of N-Type Calcium Channel Splice Isoforms in Pain

Abstract: N-type calcium channels are essential mediators of spinal nociceptive transmission. The core subunit of the N-type channel is encoded by a single gene, and multiple N-type channel isoforms can be generated by alternate splicing. In particular, cell-specific inclusion of an alternatively spliced exon 37a generates a novel form of the N-type channel that is highly enriched in nociceptive neurons and, as we show here, downregulated in a neuropathic pain model. Splice isoform-specific small interfering RNA silenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
144
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(146 citation statements)
references
References 52 publications
1
144
1
Order By: Relevance
“…Highly expressed on nociceptive fibers and within the dorsal horn of the spinal cord, CaV2.2 plays a fundamental role in relaying pain signals from the periphery. Alternative splice variants found on small diameter nociceptive neurons are associated with increased thermal and mechanical hyperalgesia (50,51). CaV2.2 is believed to be responsible for increased neurotransmitter release commonly associated with chronic and neuropathic pain conditions (1,2,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Highly expressed on nociceptive fibers and within the dorsal horn of the spinal cord, CaV2.2 plays a fundamental role in relaying pain signals from the periphery. Alternative splice variants found on small diameter nociceptive neurons are associated with increased thermal and mechanical hyperalgesia (50,51). CaV2.2 is believed to be responsible for increased neurotransmitter release commonly associated with chronic and neuropathic pain conditions (1,2,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in Ca V 2.2e[37a] mRNA levels in nociceptors should increase N-type channel sensitivity to opioids and GABA, particularly during periods of intense sensory input. Conversely, a decrease in Ca V 2.2e[37a] N-type channels, which we showed recently occurs in dorsal root ganglia following peripheral nerve injury, 13 could decrease N-type channel sensitivity to drugs and neurotransmitters. Currently, the cell-specific splicing factors that promote e37a inclusion in Ca V 2.2 mRNA are unknown.…”
Section: What Took Us So Long?mentioning
confidence: 78%
“…A recent study from the lab of Gerald Zamponi that includes contributions from Dickenson, Vergnolle and our labs, conclude: no. 13 Using splice isoform-specific small interfering RNA, Zamponi and collaborators showed that only e37a-containing N-type channels appear to mediate transmission of thermal nociception both in basal conditions (undamaged tissues) and in inflammatory or neuropathic pain models. 13 These studies suggest that selective inhibitors of e37a-containing N-type channels could be particularly effective in the treatment of certain forms of pain.…”
Section: What Took Us So Long?mentioning
confidence: 99%
See 1 more Smart Citation
“…This is driven by the established clinical link of this subtype to neuropathic pain 36 and the fact that specific knockdown of Cav2.2 ameliorates pain in chemically induced and neuropathic pain models. 37 The only marketed N-type Cav2.2 selective compound is the analgesic peptide Ziconotide, derived from the toxin of the cone snail Conus magus. Ziconotide requires intrathecal administration to be efficacious and is associated with significant side effects.…”
Section: Ion Channel Modulators For Pain Therapy In Clinical Developmentmentioning
confidence: 99%